Organization of intensive cardiac care units in Europe: Results of a multinational survey. Issue 8 (1st December 2020) - Claeys, MJ; Roubille, F; Casella, G; Zukermann, R; Nikolaou, N; De Luca, L; Gierlotka, M; Iakobishvili, Z; Thiele, H; Koutouzis, M; Sionis, A; Monteiro, S; et al.
Abstract : Background: The present survey aims to describe the intensive cardiac care unit organization and admission policies in Europe. Methods: A total of 228 hospitals (61% academic) from 27 countries participated in this survey. In addition to the organizational aspects of the intensive cardiac care units, including classification of the intensive cardiac care unit levels, data on the admission diagnoses were gathered from consecutive patients who were admitted during a two-day period. Admission policies were evaluated by comparing illness severity with the intensive cardiac care unit level. Gross national income was used to differentiate high-income countries ( n =13) from middle-income countries ( n =14). Results: A total of 98% of the hospitals had an intensive cardiac care unit: 70% had a level 1 intensive cardiac care unit, 76% had a level 2 intensive cardiac care unit, 51% had a level 3 intensive cardiac care unit, and 60% of the hospitals had more than one intensive cardiac care unit level. High-income countries tended to have more level 3 intensive cardiac care units than middle-income countries (55% versus 41%, p =0.07). A total of 5159 admissions were scored on illness severity: 63% were low severity, 24% were intermediate severity, and 12% were high severity. Patients with low illness severity were predominantly admitted to level 1 intensive cardiac care units, whereas patients with high illness severity were predominantly admitted to level 2 and 3 intensive cardiac care units. A policy mismatch was observed in 12% of the patients; some patients with high illness severity were admitted to level 1 intensive cardiac care units, which occurred more often in middle-income countries, whereas some patients with low illness severity were admitted to level 3 intensive cardiac care units, which occurred more frequently in high-income countries. Conclusion: More than one-third of the admitted patients were considered intermediate or high risk. Although patients with higher illness severity were mostly admitted to high-level intensive cardiac care units, an admission policy mismatch was observed in 12% of the patients; this mismatch was partly related to insufficient logistic intensive cardiac care unit capacity.